Implementasi Algoritma Greedy Untuk Optimalisasi Jarak Tempuh Rute Ziarah Makam Walisongo - Bachtiar, Yogi (LPPM, 2024)
Religious tourism is one of the acts of visiting a place carried out by religious people. Tourist trips sometimes face problems because some places are far apart. One important element of the pilgrimage process that must be carefully considered is the mileage of the pilgrimage route. Choosing a route that matches the distance and travel time allows many advantages, one of which is the reduction of fuel consumption during the trip. this research will try to use the Greedy Algorithm to solve the problem of optimizing the Walisongo pilgrimage tour route on the island of Java. As a result, the selected route on the Walisongo Tomb pilgrimage is S?W9?W8?W7?W6?W3?W5? W1?W1?W2 with a total travel distance of 819 Km (one way). The use of the Greedy algorithm does not always produce the shortest route, but will result in the selection of the Optimum route from one location to the next. So that it can save fuel usage and travel time between locations.